Studi Eksploratif Persepsi Mahasiswa terhadap Metode Peer Review dalam Penulisan Paragraf Akademik di Politeknik Negeri Lampung - Maisuri Hardani; Upy Raudotul Jannah; Muhamad Allan Serunting; Gilang Zulfikar (Academy of Education Journal, 2026)
This study aims to explore students’ and lecturer’s perceptions of the implementation of the peer review method in writing academic paragraphs at Politeknik Negeri Lampung. This research employed a qualitative approach with an exploratory design. The participants consisted of 40 non-language students from the Horticulture Study Program enrolled in the Indonesian Language course and one lecturer. Data were collected through classroom observation and semi-structured interviews. The findings indicate that academic paragraph writing is essential for students, particularly in completing practicum reports and final projects. The implementation of peer review involved stages of writing, exchanging drafts, providing feedback, discussion, and revision. Students showed positive perceptions toward the method, becoming more careful, critical, and open to feedback. The lecturer also perceived peer review as effective in enhancing students’ engagement and autonomy. In conclusion, the peer review method is an effective instructional strategy for improving academic paragraph writing skills among non-language students in vocational higher education.